PRACTICAL RELEVANCE OF IMPAIRED WATER AND SALT METABOLISM IN PATIENTS WITH HEART FAILURE (World Bulletin of Public Health, 2023)
A prospective study was conducted with the participation of 396 patients hospitalized for decompensation of chronic heart failure. Hyponatremia was diagnosed with a decrease in serum sodium
Keywords: hyponatremia; chronic heart failure; decompensation; severity of the disease